1990
DOI: 10.1186/bf03547544
|View full text |Cite
|
Sign up to set email alerts
|

Role of Feeding in the Treatment of Dogs with Pancreatic Degenerative Atrophy

Abstract: Fourteen dogs with pancreatic degenerative atrophy (PDA) were fed their original diets or a special diet for 2 periods of 4 weeks to compare the severety of clinical signs in relat ion to different types of diet. During the first period , the dogs were given ordinary food, and in the second period , the dogs were given only the special diet that consisted of a commercial moderate-fat, low-fiber, highly-digestible food. In addition, equal amounts of pancreatic enzymes were added into the food during both period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
6
2
Order By: Relevance
“…5,9,21 Simpson et al 9 reported that during the initial period of enzyme treatment, a low-fat diet is important for achievement of a satisfactory treatment response. Results of an earlier study 12 with low-fat diets in affected dogs, however, did not reveal an association between a decrease in fat intake and alleviation of clinical signs. In the present trial, we studied the response of dogs with EPI to excessive dietary fat.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…5,9,21 Simpson et al 9 reported that during the initial period of enzyme treatment, a low-fat diet is important for achievement of a satisfactory treatment response. Results of an earlier study 12 with low-fat diets in affected dogs, however, did not reveal an association between a decrease in fat intake and alleviation of clinical signs. In the present trial, we studied the response of dogs with EPI to excessive dietary fat.…”
Section: Discussionmentioning
confidence: 56%
“…Clinical feeding studies have yielded contrasting results on the benefits of special diets as treatment for dogs with EPI. We previously investigated 11,12 the use of 2 special diets, and our findings indicated that a highly digestible low-fiber diet alleviated certain clinical signs of EPI, but that the low-fat diet resulted in no significant changes in clinical signs. Advantages of feeding special diets were minimal in our recent study 10 of long-term treatment of EPI in dogs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations